Consecuencias del uso del implanon en mujeres menores de 30 años usuarias del subcentro de salud urbano Puyo. año 2015 - RIERA AUQUILLA, DENISSE ALEXANDRA (2016)
The purpose of this study is to determine the consequences of the use of Implanon by women younger than 30 years old in the health center of Urban Puyo in the year 2015. The design was transversal, descriptive, bibliographic and rural. The tactic of interviewing was applied and was elaborated by using questionnaires that were given to 116 women who use Implanon as a contraceptive. The following results were obtained: 31.03% of women were between the ages of 23 and 26 years of age, while adolescents registered a 20.69%. The ethnicity is 75.86% mestizo. The basic education average is 50.69%, the marital status is 35.35% married, the occupation of domestic housework is 54.31%, followed by 25% students. The prevalence of the use of Implanon is 35.80%, the timeframe of use from 0 to 5 months by 59.48%; 95,69% presented irregular and thin bleeding; 4.31% hemorrhaging; 9.52% lack of menstruation; 12.93% acne; 6.03% migraines; 18.97% weight gain; 2.59% weight loss; 75% breast tenderness; 0.86% pain in the implant location; 3.45% changes in disposition. In conclusion, the absence of menstruation found in 94.83% is the first consequence, followed by breast tenderness for 75%. The authoress completed educational activities and workshops as a nurse.